Fiscal decentralization, monetary policy, and economic growth in Indonesia: A panel data analysis - Syahrimi, Syahrimi; Hidayat, Ariodillah; Yulianita, Anna (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
The implementation of regional governance through fiscal decentralization, particularly in the management of Local Own-Source Revenue (PAD), demonstrates that regional fiscal autonomy can effectively enhance community welfare under a decentralized government structure. Using the Ordinary Least Squares (OLS) method with panel data for the period 2010–2024, this study provides empirical evidence that community welfare—measured by the growth of real Gross Regional Domestic Product (GRDP) per capita—is significantly and positively influenced by several key factors. These include Local Own-Source Revenue (PAD) with a coefficient of 0.258, Transfer Funds to Regions and Village Funds (TKDD) with a coefficient of 0.046, the Human Development Index (HDI) with a coefficient of 0.070, and Regional Investment (FDI) with a coefficient of 0.006. However, the study also identifies challenges to sustaining real GRDP growth per capita, particularly from interest rates and income inequality, which exhibit significant negative relationships with coefficients of –0.202 and –0.011, respectively. These findings suggest that disparities in population income distribution and fluctuations in borrowing costs can hinder regional economic performance. To address these challenges, regional governments must adopt fiscal incentive policies that stimulate revenue generation and investment while prioritizing human resource development. Moreover, closer collaboration with central banking authorities is essential to manage monetary policy—especially in controlling interest rates—to maintain stability and ensure balanced, inclusive regional growth.